Analisis Kelayakan Investasi Properti Proyek Pembangunan Perumahan Grand Panghegar Residence Purwakarta - Alfa Dwi Apriliani; Aji Tuhagana; Dwi Epty Handayani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
One of the advantages of property investment is protecting the purchasing power of investments and getting added value from developments such as being converted into residential buildings, however, the development of housing projects and their long implementation time mean that problems may occur that are unforeseen. The aim of this research is to determine and analyze the feasibility of property investment for the Grand Panghegar Residence Purwakarta housing development project using the Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PP) calculation methods. This type of research uses quantitative descriptive. The research results show that the project life is 2 years with an investment value of IDR 55,500,000,000, a total of 608 units for Type 30/60. The results of research calculations obtained from the investment appraisal method used were obtained as Net Present Value (NPV) = IDR 56,689,500,000 (Positive), Internal Rate of Return (IRR) = 33.72% > 12%, Payback Period ( PP) = 2, within 2 months of investment capital. The conclusion of this research states that the Grand Pahengar Residence Purwakarta Housing is an investment worthy to build and develop.